1992
DOI: 10.21273/jashs.117.1.158
|View full text |Cite
|
Sign up to set email alerts
|

Flowering, Ethylene Production, and Ion Leakage of Coffee in Response to Water Stress and Gibberellic Acid

Abstract: The effects of water stress and GA, on breaking dormancy of flower buds of coffee (Coffea arabica L.) were investigated. In the first experiment, water was withheld until the trees reached leaf water potentials (WP) of -1.20, - 1.75, -2.65, or -3.50 MPa. Water potential, ethylene production, and ion leakage of flower buds and leaf disks were examined from release from water stress until anthesis. Trees that had experienced leaf WP of less than - 2.65 MPa, and flower bud WP of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…Although rains at the end of the drying cycle can trigger flowering of woody species (Opler, Frankie & Baker 1976;Reich & Borchert 1982;Borchert 1983Borchert , 1994, our study is the first to associate these with changes in ethylene biosynthesis and the expression of regulatory genes. Both leaf and flower bud ethylene production decreased as plants advanced through the dry season (Figure 4), consistent with soil drying decreasing foliar ethylene production of rose and other herbaceous species (Morgan, He, De Greet & De Proft 1990) and flower bud ethylene production of coffee (Schuch et al, 1992) and rose (Andersen et al, 2004). Decreased shoot ethylene production was consistent with downregulation of the CaACO1-like gene ( Figure 2C), and the activity of ACO enzymes (Andersen et al 2004;Larrainzaret al 2014;Song et al 2016;Rickes, Klumb, Benitez, Braga & Bianchi 2019).…”
Section: Discussionsupporting
confidence: 63%
“…Although rains at the end of the drying cycle can trigger flowering of woody species (Opler, Frankie & Baker 1976;Reich & Borchert 1982;Borchert 1983Borchert , 1994, our study is the first to associate these with changes in ethylene biosynthesis and the expression of regulatory genes. Both leaf and flower bud ethylene production decreased as plants advanced through the dry season (Figure 4), consistent with soil drying decreasing foliar ethylene production of rose and other herbaceous species (Morgan, He, De Greet & De Proft 1990) and flower bud ethylene production of coffee (Schuch et al, 1992) and rose (Andersen et al, 2004). Decreased shoot ethylene production was consistent with downregulation of the CaACO1-like gene ( Figure 2C), and the activity of ACO enzymes (Andersen et al 2004;Larrainzaret al 2014;Song et al 2016;Rickes, Klumb, Benitez, Braga & Bianchi 2019).…”
Section: Discussionsupporting
confidence: 63%
“…From these observations they concluded that, in leeward areas of Hawaii, frequent irrigation to prevent¯owering followed by a controlled water de®cit and then re-irrigation may represent a practical way of synchronizinḡ owering and shortening the period of harvest. In a greenhouse study, Schuch et al (1992) found, however, that gibberellic acid only partially compensated for insucient water stress for¯ower initiation. Trees that experienced leaf water potentials below 72.65 MPa, and¯ower bud water potentials of about 74.0 MPa,¯owered within about nine days after irrigation.…”
Section: Flower Budsmentioning
confidence: 93%
“…Therefore, a Ψw pd of -0.71, -1.15, and -1.87 MPa was needed to induce 60%, 70%, and 80% opening, respectively, of the flower buds. The published water potential () in plants under deficit, not necessarily Ψw pd , required for breaking the dormancy of flower buds are variable, e.g., -0.80 MPa (CRISOSTO; GRANTZ; MEINZER, 1992), -1.1 to 1.2 MPa (MAGALHÃES;ANGELOCI, 1976;SILVA et al, 2009), -1.7 MPa (SILVA et al, 2009), -2.0 MPa (GUERRA; ROCHA; RODRIGUES, 2005), and -2.65 MPa (SCHUCH;FUCHIGAMI;NAGAO, 1992).…”
Section: Resultsmentioning
confidence: 99%